Developing East Java Agroindustry: Analytic Network Process Method Approach - nugroho, taufik; Rusydiana, Aam Slamet (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2018)
East Java as one of the National food barns has been able to contribute substantially in the fulfillment of National food needs through the development of food crops and horticulture sub-sector. With the potential and achievement of agriculture sector owned by East Java Province, it can improve competitiveness and improve farmer's income. But behind the potential of this great opportunity development in agroindustry in east java still leaves homework for the Government of East Java Province whether it is the problem from theexternal or internal. This research tries to identify problems in agroindustry development inEast java with Analytic Network Proccess (ANP) combined with Delphi method, including strategic solution that try to offer. ANP is a new supermatrix basedmodel developed by Saaty (2001) to map complex issues into a structured framework. Problems and strategies formed consist of several subcriteria related problems: 1) policy 2) market 3) finance 4) infrastructure 5) Research and Development and 6) Production and processing. The results show that the 3 main criteria that are key to agroindustry development in East Java are policy, infrastructure and finance. Therefore, all stakeholders including Bank Indonesia need to be concerned in these 3 issues, in order to achieve the competitive growth of East Java's global economy.